2016
DOI: 10.1161/jaha.115.002640
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prolactin and Incidence of Cardiovascular Risk Factors in the Framingham Heart Study

Abstract: BackgroundProlactin is an anterior pituitary hormone that may modulate the adverse effects of obesity. Prolactin has been associated with cardiovascular disease mortality, but less is known about whether prolactin predicts incidence of cardiovascular disease risk factors.Methods and ResultsOur sample (n=3232, mean age 40.4 years, 52.1% women) was drawn from Framingham Heart Study participants who attended 2 examinations an average of 6.1 years apart. After excluding those with elevated prolactin (>30 mg/dL for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 43 publications
3
46
1
1
Order By: Relevance
“…Furthermore, our study demonstrated that the inverse association between prolactin and type 2 diabetes risk in women remained significant after adjustment for a variety of lifestyle and reproductive factors as well as other sex and growth hormones, suggesting that prolactin may be linked to type 2 diabetes through independent pathways. Two prospective studies of men and women combined reported null associations between prolactin and type 2 diabetes risk after multivariable adjustment [18, 21]. This lack of association might be due to the limited number of incident cases ( n =163 and 78), especially among women ( n =84 and 27), and a potentially different association by sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our study demonstrated that the inverse association between prolactin and type 2 diabetes risk in women remained significant after adjustment for a variety of lifestyle and reproductive factors as well as other sex and growth hormones, suggesting that prolactin may be linked to type 2 diabetes through independent pathways. Two prospective studies of men and women combined reported null associations between prolactin and type 2 diabetes risk after multivariable adjustment [18, 21]. This lack of association might be due to the limited number of incident cases ( n =163 and 78), especially among women ( n =84 and 27), and a potentially different association by sex.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of association might be due to the limited number of incident cases ( n =163 and 78), especially among women ( n =84 and 27), and a potentially different association by sex. In fact, several recent prospective studies suggested that the associations between prolactin and risk of type 2 diabetes and the metabolic syndrome were more likely to be beneficial in women but tended to be null or even detrimental in men [1721]. The reason underlying this sex difference is unclear, as both beneficial and detrimental effects of prolactin on IR have been reported in men [12, 44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In the Framingham Heart Study, however, after patients with elevated prolactin levels had been excluded, measurement of prolactin did not provide substantial insight into cardiometabolic risk. 18 In the light of our recent studies, it seems that pleiotropic effects of hypolipidemic agents may be attenuated by some endocrine and metabolic disturbances. A negative effect on extralipid effects of statins was exerted by untreated subclinical hypothyroidism and by low vitamin D status.…”
mentioning
confidence: 99%
“…Finally, in the population‐based Study of Health in Pomerania, prolactin concentrations were correlated with all‐cause mortality and cardiovascular mortality . In the Framingham Heart Study, however, after patients with elevated prolactin levels had been excluded, measurement of prolactin did not provide substantial insight into cardiometabolic risk …”
mentioning
confidence: 99%